Taking play seriously : a challenge of learning - Lillemyr, Ole Fredrik (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"In the book, the author is focusing the importance of play for children from 0 years up to 8-12 years of age, e.g. in ECE centers and elementary schools. In particular, the importance of play for learning, through motivation as related to self-competence, inspiration and engagement. In this second edition, the author is emphasizing more thoroughly the importance of play as a challenge of learning, with implications for children, as well as for teachers. Further, the author is discussing how meaning making in children's production of multi-module narrative products can contribute to their digital personal formation. The selection of theories presented in the second edition is somewhat expanded, and in the end the author is presenting a few important educational challenges of the field of children's play"--